Sesquiterpene Lactams and Lactones With Antioxidant Potentials From Atractylodes macrocephala Discovered by Molecular Networking Strategy - Wang, Pan; Zhao, Yi-nan; Xu, Rui-zhu; Zhang, Xiao-wei; Sun, Yi-ran; Feng, Qing-mei; Li, Zhong-hua; Xu, Jiang-yan; Xie, Zhi-shen; Zhang, Zhen-qiang; E, Heng-chao (Frontiers in Nutrition, 2022)
Atractylodes macrocephala rhizome (called Bái-zhú in China) has a long history as a functional food and herbal medicine in East Asia, especially China. Sesquiterpenoids are one of the main active compounds of Atractylodes macrocephala rhizome. This study aimed to explore the unknown sesquiterpenoids of A. macrocephala rhizome using a molecular networking strategy. Two new nitrogen-containing sesquiterpenoids, atractylenolactam A (1) and atractylenolactam B (2), and 2 new sesquiterpene lactones, 8-methoxy-atractylenolide V (6) and 15-acetoxyl atractylenolide III (7), along with 12 known analogs (3-5 and 8-16) were discovered and isolated. All the structures were assigned based on detailed spectroscopic analyses. The absolute configurations of 1, 2, 6, and 7 were established by time-dependent density functional theory ECD (TDDFT-ECD) calculations. All these compounds had different degrees of concentration-dependent activating effects on nuclear-factor-E2-related factor-2 (Nrf2).